(untitled) (Journal of the College of Basic Education, 2024)
This study aimed to identify (organizational commitment according to Clayton’s theory among special education teachers), so the following research objectives were formulated: - 1-The level of organizational commitment according to Clayton’s theory among special education teachers in Baghdad Governorate schools on the Rusafa side (first, second, and third). 2-Identifying statistically significant differences in organizational commitment among special education teachers according to the gender variable (males – females). The research community included all members of the teaching staff in primary schools in Baghdad Governorate, in addition to (Rusafa First, Second, and Third) for the academic year (2023-2024), who numbered (58) male and female teachers. The research sample was chosen by random stratified method and consisted of (40) A male and female teacher from the research community, and to achieve the research objectives, the researcher adopted (Clayton Organizational Commitment Scale), which consists of three domains the first domain, consisting of (7) items, the second domain, consisting of (7) items, the third domain, consisting of (7) items. paragraph), the researcher chose the items whose answers were appropriate for special education teachers and free from cultural factors, with the possibility of applying them, and taking into account the time allotted for applying the scale. The number of items reached (21), and after presenting it to the experts, all items of the scale were kept in light of The theoretical concept of organizational commitment.